2019
DOI: 10.1088/1742-6596/1358/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Oil Palm Leaf Fibre in Paper-making Industry

Abstract: Utilization of agro-based fibre for paper making has been the subject of interest in order to expand the usage of renewable resources as well as reduced the dependence on wood pulp. As one of the major countries in palm oil production, some of the waste from the oil palm plantation like the oil palm fronds, empty fruit bunches, and its leaf is a potential source of non-wood industry which can be used as raw material in the paper industry manufacture. This study was done to examine the potential of palm leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Meanwhile, both 75EFB (375 counted pore particles) and 100EFB (234 counted pore particles) have an average area of pore size 0.37 mm 2 (±0.32). The small variations from the average are of pore size obtained were mostly du e to the uneven distribution of pulp when moulding the paper (Soloi & Hou, 2019). Additionally, a higher tensile index may denote a lower cellulose content (Aremu, Rafiu & Adedeji, 2015).…”
Section: Grammagementioning
confidence: 99%
“…Meanwhile, both 75EFB (375 counted pore particles) and 100EFB (234 counted pore particles) have an average area of pore size 0.37 mm 2 (±0.32). The small variations from the average are of pore size obtained were mostly du e to the uneven distribution of pulp when moulding the paper (Soloi & Hou, 2019). Additionally, a higher tensile index may denote a lower cellulose content (Aremu, Rafiu & Adedeji, 2015).…”
Section: Grammagementioning
confidence: 99%
“…Most of the components, especially lignin, are removed through delignification to obtain pure pulps that consist of cellulose and some hemicelluloses fibers during the treatment process. The key reaction in the delignification is the cleavage of the ether bond (Soloi and Hou 2019). Chen and Wang 2017 classified delignification into initial, bulk and residual stages.…”
Section: Delignification Processmentioning
confidence: 99%
“…Low lignin content is important in the pulp industry since good quality of paper can be achieved with low lignin content (Laftah & Abdul Rahaman, 2015). Previous study by Soloi & Hao (2019) has shown that oil palm leaf fibre can be moulded into paper sheet without any processing aid such as starch solution as a binder. The tensile strength of the paper was low.…”
Section: Introductionmentioning
confidence: 99%